Cost-Minimization Analysis of Medications Used in the Management of End-stage Renal Disease - Naik, Jarupala Gangadhar; Dharmagadda, Sreedhar; Murugundi, Pradeep Manohar; Ligade, Virendra; Nagaraju, Shankar Prasad; Kulkarni, Manjunath (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim/Background: Several branded pharmaceuticals and generic medicines are available in the market for the management of End-Stage Renal Disease (ESRD) as a supportive care, and clinicians are unaware of the cost minimization and cost consequences aspects of these medications. Thus, this study aimed to compare the prices of branded versus generic medicines for ESRD treatment and to present the cost savings with a generic alternative. Materials and Methods: A prospective observational study was conducted among ESRD patients from three different tertiary care teaching hospitals in South India. The cost of branded pharmaceuticals were determined using the most recent current index of medical specialties, while the prices of generic medicines were accessed using the Pradhan Mantri Bhartiya Jan Aushadhi Pariyojana scheme, 2022. Results: The data were collected from 385 patients with ESRD. All Jan Aushadhi generic medicines were less expensive when compared to the branded medicines. The cost of ESRD medicines accessible in India varies greatly. The greatest difference in percentage cost savings were noted with amlodipine 5 mg tab (93.03%), voglibose 0.2mg/tab (88.10%), calcium carbonate + Vitamin D3 supplements 500 mg tab (80.27%), torsemide 10 mg tab (78.01%), and hematopoietic agent, erythropoietin 2000 U/inj (75.38%). Conclusion: The haematopoietic medicines and antidiabetic insulin injections were the most expensive medicines among the study population. Our research indicates that replacing the generic medicines with the branded medicines could help in reducing the cost burden. Healthcare professionals may consider prescribing generic medicines for cost-savings.
Keywords: Pharmacoeconomics; Cost minimization; End stage renal disease; Antibiotics; Insulin; Jan Aushadhi